Geographic Information System (GIS) mapping project in Pedro Vicente Maldonado Ecuadorian scientific station Antartica base (Greenwich Island) Antarctic Peninsular - Fauzi, R.; Hussin, A. (2008)
Essentially, the outputs from the GIS project in the expedition were GIS database, spatial maps and 3D terrain model of the Pedro Vicente Maldonado Ecuadorian Scientific Station Antarctica Base area. GIS techniques were used for developing the data base, maps and 3D model. The main source of data was obtained by a Global Positioning System (GPS) survey using a kinematic GPS (GPS-RTK) which allowed continuous point mapping in the terrain. GPS units were utilized in the collection of spatial data for all field works. The coordinates obtained were used to produce a point map which is then exported into GIS software where the proximity of cartographic phenomena and boundaries were mapped. All the collected data were subsequently gathered to develop the GIS database and to compile and generate different maps to test for spatial and temporal relationships. The developed GIS database can be used in conjunction with other ecological datasets to provide biogeographically information, potential range distribution, and sampling adequacy. The database is applicable to geographical management and to multi-disciplinary research projects.